Challenges and Advancements for AR Optical See-Through Near-Eye Displays: A Review - Xia, Xinxing; Guan, Frank Yunqing; Cai, Yiyu; Magnenat Thalmann, Nadia (Frontiers in Virtual Reality, 2022)
Optical see-through near eye display (NED) technologies for augmented reality (AR) have achieved significant advancements recently with investments from both academia and industry. Although various AR NED products have been successfully commercialized and even deployed into applications, there are still challenges with present AR NED technologies (e.g. limited eyebox, fixed focus, bulky form factors). In this review, we present a brief overview of leading AR NED technologies and then focus on the state-of-the-art research works to counter the respective key challenges with each of the leading AR NED technologies. We also introduce a number of emerging technologies that are worthy of close study.